1997
DOI: 10.1002/(sici)1098-2795(199709)48:1<95::aid-mrd12>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol species as messengers and substrates for phosphatidylcholine re-synthesis during Ca2+-dependent exocytosis in boar spermatozoa

Abstract: We have investigated pathways of lipid metabolism in spermatozoa and generation of various metabolites with potential messenger functions during exocytosis stimulated with A23187/Ca2+. Stimulation of boar spermatozoa resulted in a considerable rapid increase in saturated/unsaturated 1,2‐diacylglycerol (1,2‐SU‐DAG) and, concomitantly, a substantial reduction in disaturated 1,2‐diacylglycerol (1,2‐DS‐DAG), and in phosphatidylcholine (PC). These changes preceded the onset of exocytosis. Phosphatidic acid was some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…The most important function of DAG in sperm is its participation in the acrosome reaction. Diacylglycerols have been reported to be engaged in membrane fusion during acrosomal exocytosis [174][175][176], which is consistent with previous studies in other cell types [177][178][179]. In particular, PC-derived DAG is thought to be related to AR exocytosis in boars [176].…”
Section: Diacylglycerolssupporting
confidence: 89%
See 1 more Smart Citation
“…The most important function of DAG in sperm is its participation in the acrosome reaction. Diacylglycerols have been reported to be engaged in membrane fusion during acrosomal exocytosis [174][175][176], which is consistent with previous studies in other cell types [177][178][179]. In particular, PC-derived DAG is thought to be related to AR exocytosis in boars [176].…”
Section: Diacylglycerolssupporting
confidence: 89%
“…Diacylglycerols have been reported to be engaged in membrane fusion during acrosomal exocytosis [174][175][176], which is consistent with previous studies in other cell types [177][178][179]. In particular, PC-derived DAG is thought to be related to AR exocytosis in boars [176]. Another study revealed that DAGs promoted intraacrosomal calcium efflux and triggered exocytosis of permeabilized human sperm [180].…”
Section: Diacylglycerolssupporting
confidence: 87%
“…The stimulation with different inducers showed an increase in DAG concentration in human sperm treated with progesterone, calcium ionophore A23187 and ZP (Roldan and Murase ), in mouse (O'Toole et al. ), in ram (Roldan and Harrison ) and in boar (Vázquez and Roldan ).…”
Section: Discussionmentioning
confidence: 99%
“…The negative control represents SAR (13.9%). Results are expressed as the mean AE SEM of 5 experiments with different animals A23187 and ZP(Roldan and Murase 1994), in mouse(O'Toole et al 1996), in ram(Roldan and Harrison 1992) and in boar (V azquez andRoldan 1997).…”
mentioning
confidence: 99%
“…This included lower levels of diacylglycerol (DAG) and sphingomyelin (SM) and higher levels of phosphatidylcholine (PC) and ceramide (Cer). Since these lipids have been shown to play a major role in capacitation, we hypothesized that the variant-induced altered sperm membrane composition is causative for infertility [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%